El Expreso Polar - Van Allsburg, Chris (Caracas Country : Ekare Banco del Libro, 1991)
A magical train ride on Christmas Eve takes a boy to the North Pole to receive a special gift from Santa Claus.
Translation of: The Polar Express.
K-3
LAUSD Resource list - Languages other than English
Keywords: Santa Claus -- Fiction; Christmas -- Fiction; Spanish language materials; Santa Claus -- Fiction; Christmas -- Fiction; Spanish language; North Pole -- Fiction; North Pole -- Fiction